Old and new specimens confirm the presence of the Tanintharyi rock gecko Cnemaspis tanintharyi Lee, Miller, Zug and Mulcahy, 2019 in Thailand (Squamata: Gekkonidae) - Pawangkhanant, Parinya; Kaosung, Andaman; Naiduangchan, Mali; Suwannapoom, Chatmongkon; Lee, Justin L. (Zootaxa, 2026)
The Tanintharyi rock gecko Cnemaspis tanintharyi was described from two localities in southern Myanmar (Burma). The authors of that study were aware of historical “South Asian” Cnemaspis records from adjacent Thailand but could not confirm their taxonomic status. Here, we examined the specimens that correspond to these records and confirm they are conspecific with C. tanintharyi. In conjunction, we provide new localities, morphological data and live photographs of this species. Several mistakes in the original description of C. tanintharyi are corrected in hopes they provide clarification for future taxonomic workers. The new occurrences of this species significantly expand its geographic distribution. As a result, we recommend an updated status of “Near Threatened” based on the criteria adopted by the IUCN Red List.